Housing for Female Factory Workers: The Association between Renting Accommodation and Satisfaction with Income and Living Conditions - Quynh Thuy Nguyen; Thuy Thi Thu Tran; Chinh Thi Thuy Phan; Tuan Cong Pham (AIMS Press, 2016)
Background: Vietnam has experienced a strong wave of migrants to urban and industrialized areas. This is a challenge for both local and national governments, which need to address the problems of the poor and socially marginalized, including providing housing for rural-to-urban migrants. Poor housing and the economic burden of house renting are increasingly recognized as determinants of both physical and mental health. Objectives: This paper examined the association between renting accommodation and income satisfaction and living conditions of female workers in light manufacturing industries in Vietnam. Methods: A cross-sectional study was implemented with quantitative survey of 2,818 female workers in 10 light manufacturing factories in 3 industrial zones by a self-administered questionnaire. Results: Over 38% of female workers had to rent accommodation. The average expense for accommodation, water and electricity accounted for 30.1% of renters' income, which is 7.2% (CI 95%, 5.3-9.3%) higher than for non-renters. A higher proportion of renters than non-renters considered their income was unstable and insufficient for living costs. In addition, only 7.2% of renters reported that their living conditions were suitable, notably lower than non-renters (22.4%). Conclusion: The study showed the economic burden of renting accommodation on workers' income satisfaction and living conditions. The findings have implications for an adequate housing access strategy for workers including the integration of housing development in the planning and development of industrial zones and factories.